2012
DOI: 10.1002/bmb.20590
|View full text |Cite
|
Sign up to set email alerts
|

Integration of basic sciences in health's courses

Abstract: Concepts from disciplines such as Biochemistry, Genetics, Cellular and Molecular Biology are essential to the understanding and treatment of an elevated number of illnesses, but often they are studied separately, with no integration between them. This article proposes a model for basic sciences integration based on problem‐based learning (PBL) and compares failure rate, global final grade, approved student final grade, grade distribution and students' satisfaction with teacher conduction between integrated cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 19 publications
1
21
0
7
Order By: Relevance
“…Nevertheless, sometimes it may be arduous to allow the fact that the increasing knowledge of biological sciences may be incorporated into clinical sciences [3]. In this way of thinking several experiences have recently been described [4][5][6]. In 2 Journal of Biomedical Education of students concerning the utility of basic sciences for their future clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, sometimes it may be arduous to allow the fact that the increasing knowledge of biological sciences may be incorporated into clinical sciences [3]. In this way of thinking several experiences have recently been described [4][5][6]. In 2 Journal of Biomedical Education of students concerning the utility of basic sciences for their future clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…These 40 studies reported integrated educational interventions employed across medicine (n=28) [10-12, 16-21, 23-25, 28, 29, 31, 33, 34, 36, 38-41, 44-49], pharmacy (n=11) [13-15, 26, 27, 29, 30, 32, 35, 37, 42],and dentistry (n=1) [22] in institutions worldwide: United States of America (n=14) [11, 13-15, 24-27, 29, 30, 32, 40, 42, 46], India (n=7) [10, 18-20, 28, 33, 41], United Kingdom (n=6) [22,35,37,39,43], Middle East (n=4) [16,17,23,31], the Netherlands (n=4) [31,44,48,49], Belgium (n=2) [45,47], and one from each of: Stockholm [12], Brazil [21], Germany [36], and Korea [38].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The number of students experiencing the integrated educational activities was not always described, but where included, cohorts varied from relatively small, approximately 30-40, to very large, approximately 1000-2000 students. Most studies, (n=34) adopted surveys to capture student feedback [10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][34][35][36][37][38][39][43][44][45][46][47][48][49], six studies employed student interviews or focus groups [11,12,27,29,36,37] and 24 assessed student performance at a terminal assessment [10,14,15,17,18,21,[23]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations